Pengembangan Pegawai Peintervening: Gaya Kepemimpinan Efektif dan Inklusivitas Keragaman Terhadap Kinerja Pegawai Pada Dinas Pendidikan dan Kebudayaan Kota Padang - Tiara Alexta; Chintya Ones Charli; Yoga Pratama Putra; Gilbert Yonanda Zega (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to test how much influence effective leadership style and diversity inclusivity have on employee performance with employee development as an intervening variable in the education and culture office of Padang City. The data collection method is through surveys and distributing questionnaires, with a sample of 94 respondents. The analytical method used is structural equation modeling using smartpls. The research results showed that there was a significant influence of effective leadership style on employee development. There is a significant influence of diversity inclusivity on employee development. There is a significant influence of effective leadership style on employee performance. There is an insignificant effect of diversity inclusivity on employee performance. There is a significant influence of employee development on employee performance. Employee development mediates the influence of effective leadership style on employee performance. Employee development mediates the effect of diversity inclusiveness on employee performance.